Predictive Analysis: Academic Resilience as a Determinant of Mathematics Achievement among Senior Secondary School Students in Nigeria - Duru, Darlington Chibueze; Obasi, Chinedu Victor; Oguoma, Chinyere (S&Co Publishing, 2024)
Mathematics is considered a key foundation for scientific knowledge required for the development of any nation. Poor mathematics achievement has been reported nationally. This paper was designed to investigate academic resilience as a determinant of mathematics achievement among senior secondary school students in Owerri municipal council of Imo State. A correlational design was used for the study. The study comprised a population of 32,068 students in public secondary schools in Owerri Municipal Council of Imo State. A sample of 180 SSII students was drawn from the population, using simple random sampling. Two instruments were used for data collection in this study. They are: the Academic Resilience Scale (ARS) for secondary school students was developed by Martin and Marsh with a Cronbach reliability coefficient of 0.74, and the Mathematics Achievement Proforma (MAP). Descriptive and inferential statistics including simple linear regressions were used for data analysis. The findings showed that academic resilience positively and significantly predicted mathematics achievement irrespective of gender. It was recommended to prepare and encourage students to be resilient, with the spirit of resilience inculcated at a young age, as this helps them in life and positively predicts mathematics achievement.